(untitled) (Hekima Review, 2024)
Formation is foundational to religious life. It allowscandidates to discover, acquire, assimilate and deepen their religious identity. Since family and societal culture constantly change, high-quality ongoing formative programs are indispensable. Yet, despite the aim of formation and the Church’s guidelines on holistic and transformativeformation, formation challenges appear perennial and seem to call fora collaborative approach. This article highlights some challenges to theholistic and transformative formation, indicating magisterial responses. Italso elucidates the Church’s invitation for a collaborative approach andbuttresses the synergetic approach of Hekima University College (HUC)towards the transformative formation of African women religious.